2020
DOI: 10.3991/ijep.v10i1.11661
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Female Students for Computer Science by Means of Robot Workshops

Abstract: As women belong to a minority in computer science, this work aims to provide possible STEM education initiatives for middle to high school students. These initiatives are designed for institutions to contribute to increasing the proportion of women in computer science by using robots. Through applying these initiatives, institutions such as computer science faculties can help to reduce the gender imbalance, increase diversity and the amount of computer science specialists, who are requested immensely. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The results of Cassidy's (2016) research about academic resilience showed that, for British undergraduates, gender resulted in small but insignificant differences. Research has shown that the dominant western perception of computer science, especially programming, is that it is a masculine endeavour (Keller & John, 2020). Female students tend to lack the curiosity, motivation and integration capabilities for programming, and they lack the confidence in their ability to code properly (Malik & Coldwell-Neilson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results of Cassidy's (2016) research about academic resilience showed that, for British undergraduates, gender resulted in small but insignificant differences. Research has shown that the dominant western perception of computer science, especially programming, is that it is a masculine endeavour (Keller & John, 2020). Female students tend to lack the curiosity, motivation and integration capabilities for programming, and they lack the confidence in their ability to code properly (Malik & Coldwell-Neilson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There have been some other initiatives and studies in similar directions. For example, there was an initiative carried out in a workshop [15] for middle to high school students, which was aimed to increase the proportion of women in computer science by using robots. The workshop introduced programming concepts for robotic applications, through a presentation with some programming code in Python.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Several other studies and initiatives have explored similar approaches. One initiative was a workshop [15] aimed at increasing the number of women in computer science at the middle and high school level. The workshop introduced programming concepts for robotic applications using a presentation with Python.…”
Section: Introductionmentioning
confidence: 99%